The social benefits of private infectious disease-risk mitigation - Benjamin R. Morin; Charles Perrings; Ann Kinzig; Simon Levin (Theoretical Ecology, 2015)

Linking ecosystem characteristics to final ecosystem services for public policy - Christina P. Wong; Bo Jiang; Ann P. Kinzig; Kai N. Lee; Zhiyun Ouyang (Ecology Letters, 2015)
Governments worldwide are recognising ecosystem services as an approach to address sustainability challenges. Decision‐makers need credible and legitimate measurements of ecosystem services to evaluate decisions for trade‐offs to make wise choices. Managers lack these measurements because of a data gap linking ecosystem characteristics to final ecosystem services. The dominant method to address the data gap is benefit transfer using ecological data from one location to estimate ecosystem services at other locations with similar land cover. However, benefit transfer is only valid once the data gap is adequately resolved. Disciplinary frames separating ecology from economics and policy have resulted in confusion on concepts and methods preventing progress on the data gap. In this study, we present a 10‐step approach to unify concepts, methods and data from the disparate disciplines to offer guidance on overcoming the data gap. We suggest: (1) estimate ecosystem characteristics using biophysical models, (2) identify final ecosystem services using endpoints and (3) connect them using ecological production functions to quantify biophysical trade‐offs. The guidance is strategic for public policy because analysts need to be: (1) realistic when setting priorities, (2) attentive to timelines to acquire relevant data, given resources and (3) responsive to the needs of decision‐makers.